A New Stress Field Model for Semiclosed Crack under Compression considering the Influence of T-Stress. (10th October 2022) - Feng, Mingyu; Zhou, Xiaoguang; Zhang, Yanbin; Wu, Saifeng
Abstract : Compression is a typical stress condition for cracks in deep-water structures, where the cracks tend to close from a nonclosed state, due to a certain gap that exists between the surfaces on both sides of cracks. The stress field models around the crack have been established in previous studies, while the crack surfaces are simply assumed in a nonclosed or full-closed state. In fact, the cracks inside deep-water structures are usually in a semiclosed state, leaving the reliability of calculation results in risk. To reflect the actual state of crack, a comprehensive stress field model around the semiclosed crack is established based on the complex potential theory, and the stress intensity factor K II at the crack tip related to the closure amount of crack surfaces, deep-water pressure, friction coefficient in the closed region, and crack inclination angle is derived. The analytical solution of the stress field around the semiclosed crack contains three T -stress components, i.e., T x, T y, and T x y . The rationality and effectiveness of the proposed stress field model are verified by the isochromatic fringe patterns around the crack obtained from the photoelastic experiment. It reveals that the proposed model can reasonably predict the evolution of the stress field with the closure amount of crack under constant and variable stress conditions.